PLANT VEGETATION ANALYSIS USING the LINE TRANSECT METHOD in GLEE REULEUNG AREA, LEUPUNG DISTRICT, ACEH BESAR - Fadhillah, Nada; Suwarniati, Suwarniati; Zahara, Meutia; Aini, Qurratu; Muslim, Muslim; Rizki, Cut Novrita (Jurnal Biologi Sains dan Kependidikan, 2021)
Plants are organism that can produce organic materials needed for it self and another organism. The role of plants as the producers is very important for food chain in life. There are various types of plants that are very useful as the producers in Glee Reulueng, Leupung District, Aceh Besar. This study aims to determine the diversity, identify and analyze the composition of species, plants, and tree structures of forest vegetation. The method used were direct observation using the line transect. The plants observed were only poles and trees. The minimum size of pole type has a total height of 5 m and 10 m for trees. Data analysis was carried out by looking for density, frequency, dominance, important value index (INP) and some dominance ration (SDR). The results showed that there are 30 species of plant vegetation in Glee Reuleung, the Morisita distribution index of plant vegetation is random with a value of id = 1 and the diversity of plant species is classified as moderate, with the highest value in plot 1 (? = 2.91) and is lowest in plot 3 (?= 2.36)Keywords: Plant diversity, Line transect, forest vegetation, Glee Reuleung